The bridge on the River Kwai - Wilson, Michael 1914-1978; Foreman, Carl; Holden, William 1918-1981; Guinness, Alec 1914-2000; Hawkins, Jack 1910-1973; Hayakawa, Sesshu 1889-1973; Donald, James 1917-1993; Sears, Ann; Horne, Geoffrey; Boulle, Pierre 1912-1994; Arnold, Malcolm
British soldiers captured by the Japanese during World War II are forced to construct a strategic railroad bridge which a commando team is instructed by the British High Command to destroy